BIBLIOMETRIC ANALYSIS: DEVELOPMENT AND DYNAMICS OF PUBLIC SERVICE RESEARCH FOR PEOPLE WITH DISABILITIES - Artanti, Cheryl Amelia; Permatasari, Indah; Imania, Katriza; Thamrin, M. Husni (Jurnal Sosiologi Dialektika Sosial, 2024)
This study aims to present a bibliometric analysis of the research development on public services for disabilities from 2015 to 2023. The study utilizes data from the Scopus database using the keyword "Public services for disabilities" to identify and analyze relevant journal articles, conference proceedings, and books. The search method involves using these keywords in the title, abstract, and keywords of articles. Collected data includes the annual publication count, document types (journal articles, conference proceedings, books), influential primary authors, patterns of co-authorship among authors, and international collaboration among research institutions. Results of the analysis encompass trends in publications in this field, predominant document types, influential primary authors, and patterns of author collaboration. Key findings indicate a significant increase in journal article publications throughout the period, with specific attention to health, policy, technology, and social support aspects for individuals with disabilities. The analysis also highlights the development of specific topics receiving greater attention from researchers. This study provides insights into research dynamics in this field and identifies areas needing further attention to enhance inclusivity and quality of life for individuals with disabilities globally.